Servicecape Analysis To Customer Satisfaction In Delivery Service Company With Customer Trust As Intervening Variable - Hardi Mulyono; Muhammad Hilman Fikri; Abd Rasyid Syamsuri (Politeknik APP Jakarta, 2023)
The number of people who send goods to each other makes delivery services very important. The development of internet technology has a great contribution to the community need for goods delivery services. For buying and selling goods business , it is not only limited to face-to-face but also be done through online media. This research was conducted using sampling technique namely convenience sampling with consideration of convenience, such as respondents who are easier to find by researchers (Sugiarto, 2011). Respondents in this study were Costumer s who use delivery service companies with the following criteria: Have used delivery services in the last six months. The number of respondents used was as many as 120 respondents with 22 types of attributes in the questionnaire. The results of the study showed that there was a positive and significant relationship between the servqual variable and Costumer trust; there was no positive and significant effect between servicecape variables on Costumer trust; service quality on Costumer loyalty did not have a significant and positive effect; there was no effect of servicecape on Costumer loyalty; there was a positive and significant effect of the Costumer trust variable on Costumer loyalty.